Young Men’s Shame about Their Desire for other Men Predicts Risky Sex and Moderates the Knowledge – Self-Efficacy Link - Park, Mina; Anderson, Janeane N.; Christensen, John L.; Miller, Lynn Carol; Appleby, Paul Robert; Read, Stephen John (Frontiers in Public Health, 2014)
Background: Recent findings suggest that a strong negative social emotion (i.e., shame) increases YMSM’s sexual risk-taking. Unchangeable shame (e.g., desire for other men) might undermine (moderate) the link between knowledge and self-efficacy or between self-efficacy and unprotected anal intercourse (UAI): This may be less likely for changeable shame (e.g., shame about risky sexual behavior). Aim: To test the hypotheses that shame (i.e., sexual desire shame), but not shame about behavior (i.e., sexual behavior shame), will be positively related to UAI and will moderate the relationship between knowledge and self-efficacy and/or self-efficacy and UAI among YMSM. Method: In an online national study, 1177 young adult (18-24 year old) MSM reported one or more acts of UAI in the past 90 days with a casual partner. Eligible MSM filled out a survey in which they provided information about their knowledge of safer sex, self-efficacy for safer sex, reported levels of shame, and reported past 90-day UAI. Results: Sexual desire shame was negatively correlated with knowledge and self-efficacy and positively correlated with UAI: The pattern reversed for sexual behavior shame. Sexual desire shame significantly lowered the knowledge to self-efficacy and the self-efficacy to UAI links. Sexual behavior shame also reduced the link from knowledge to self-efficacy, but not the self-efficacy to UAI link. Conclusion: The present study shows that there are different types of shame that may produce different effects with different implications for health behavior. Sexual desire shame may better reflect an emotion that is activated prior to risky behavior (e.g., when men reflect upon or feel desire for another man). Sexual behavior shame, on the other hand, better reflects what has already happened: Thus, those higher in knowledge, efficacy, and therefore safer sex are least likely to experience shame behavior.